PENGAMANAN WEBSITE E-COMMERCE MENGGUNAKAN MULTI-FACTOR AUTHENTICATION - Muhammad Adi Nugraha; Desi Arisandi; Novario Jaya Perdana (Fakultas Teknologi Informasi Universitas Tarumanagara, 2021)
Data security is very important and privacy for every user because there is sensitive information so it must be safe from irresponsible parties. One method that can secure user account data is Multi-Factor Authentication. E-commerce applications using Multi-Factor Authentication can secure their user accounts. This discussion is about creating website-based e-commerce applications that users can use to buy smart phone products. This E-commerce website application can secure users through 3 login steps. The login mechanism presented in this e-commerce website application is login with password, login with OTP code, and finally login with personal questions. The experimental results show that using the multi-factor authentication method provides good security for user accounts